Absorpcija makrohranil, mikrohranil in zdravilnih učinkovin - Žakelj, Simon (Farmacevtski vestnik, 2020)
The spectre of drug bioavailability reminds us that the intestinal absorption is not guaranteed. Any substance that does not dissolve or does not dissolve fast enough, that does not diffuse through the gastrointestinal mucosa or diffuses too slowly, will have low bioavailability. As most nutrients, unlike the active pharmaceutical ingredients, only poorly diffuse through the intestinal mucosa via passive mechanisms, their absorption is enabled by efficient and well controlled selective processes.
Keywords: absorpcija iz prebavnega trakta; absorpcija zdravilnih učinkovin; makrohranila; mehanizmi absorpcije hranil; mikrohranila; Zdravilne učinkovine